Analisis Kinerja Pegawai pada Proses Reimbursement PPH 23 di Terminal Petikemas Surabaya - Evelyn Cornelia (Journal of Citizenship, 2025)
This study aims to analyze employee performance in the PPh 23 reimbursement process at PT Terminal Petikemas Surabaya. The background of this study is based on the importance of the role of employees in carrying out their duties properly and orderly in accordance with tax administration. This study uses Campbell's performance theory, which takes four dimensions, namely job-specific task proficiency, written and oral communication proficiency, demonstrating effort, and maintaining personal discipline. This study uses a descriptive qualitative method, with data collected through interviews with the employees involved, supported by the author's observations in the field. The results show that overall employee performance has been good. Employees demonstrate adequate technical skills in carrying out their specific tasks, communicate effectively, show high work enthusiasm, and comply with company procedures and regulations. These four dimensions of performance support each other and contribute to the smooth process of PPh 23 reimbursement at PT Terminal Petikemas Surabaya. However, several obstacles were still found, so that the company is expected to be able to improve in order to minimize existing obstacles.